2022
DOI: 10.3923/pjbs.2022.993.1000
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Sensory Evaluation of Balady Bread Supplemented with Watermelon Rinds Flour and its Anti-Hyperlipidemic Effect in Male Albina Rats

Abstract: Background and Objective: Watermelon is a good source of minerals, vitamins and dietary fibers. It has been considered a health benefits effect due to the high amount of antioxidants and phytonutrients such as phenolics, flavonoids, phytosterols and other medicinal compounds which decrease the risk of cardiovascular, diabetes and cancer. This research was carried out to study the effect of wheat flour (WF) supplemented with different levels of watermelon rinds flour (WRF) on the chemical and organoleptic prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The enrichment of red algae was studied by Yousef et al 20 , while Hussein et al 21 assessed low-protein variants. Ingredients like seed coats, rice bran, and watermelon rinds were experimented with to assess changes in chemical and sensory properties, as well as potential health benefits 22 25 . Also, the color attributes of Baladi bread can be altered by ingredients and processing techniques.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The enrichment of red algae was studied by Yousef et al 20 , while Hussein et al 21 assessed low-protein variants. Ingredients like seed coats, rice bran, and watermelon rinds were experimented with to assess changes in chemical and sensory properties, as well as potential health benefits 22 25 . Also, the color attributes of Baladi bread can be altered by ingredients and processing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of coriander seeds, nano-powders, and red algae on color parameters was highlighted 17 , 20 , 28 . The impact of watermelon rinds and rice bran was assessed 23 , 25 , and wheat grain fertilization techniques were compared 29 . However, olive oil amounts did not significantly change ciabatta bread color 30 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors added watermelon purée and juice to the wheat bread and concluded that these additions enriched the bread with nutrients [14]. The bread was additionally enriched with watermelon rind powder, which is expected to enhance its superior qualities [15,16].…”
Section: Introductionmentioning
confidence: 99%